A Review of Acute Coronary Syndrome and its Potential Impact on Cognitive Function. Issue 1 (4th August 2021) - Kasprzak, Dominika; Rzeźniczak, Janusz; Ganowicz, Teresa; Łuczak, Tomasz; Słomczyński, Marek; Hiczkiewicz, Jarosław; Burchardt, Paweł
According to the World Health Organization (WHO) forecasts, in 2030, the number of people suffering from dementia will reach 82 million people worldwide, representing a huge burden on health and social care systems. Epidemiological data indicates a relationship between coronary heart disease (CHD) and the occurrence of cognitive impairment (CI) and dementia. It is known that both diseases have common risk factors. However, the impact of myocardial infarction (MI) on cognitive function remains controversial and largely unknown. The main goal of this study is to attempt to summarize and discuss selected scientific reports on the causes, mechanisms and effects of CI in patients after acute coronary syndrome (ACS), especially after MI. The risk of CI can increase in patients after ACS, and can therefore also adversely affect the further course of treatment. A late diagnosis of CI can lead to serious clinical implications, such as an increase in the number of hospitalizations and mortality.